2020
DOI: 10.38112/agw.2020.v08i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield performance of oyster mushroom (Pleurotus ostreatus) on different substrates

Abstract: Oyster mushroom (Pleurotus oestratus) has outstanding flavor and taste with fan shaped pileus which is rich source of both macro and micro nutrients. It is of paramount importance to choose appropriate substrates in a given place to grow oyster mushroom successfully. The experiment was conducted at Bangaun, Lamahi, Dang, Nepal during 2018-19 to study the growth performance of oyster mushroom on locally available substrates as well as to find out the best substrate. The substrates used in the experiment were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Cellulose and lignin in the substrate were important components deciding the yield of sporocarp. A good substrate should be rich in nutrients, have good aeration and water holding capacity and have high lignocellulosic content (Sharma et al 2013, Dhakal et al 2020. Wheat straw and maize straw proved to be the best substrate and provided highest yield and biological efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose and lignin in the substrate were important components deciding the yield of sporocarp. A good substrate should be rich in nutrients, have good aeration and water holding capacity and have high lignocellulosic content (Sharma et al 2013, Dhakal et al 2020. Wheat straw and maize straw proved to be the best substrate and provided highest yield and biological efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Holes were used for diffusion of gases and heat generated inside the bags. Then, mouth of each bag was tied with a thread (Dhakal et al, 2020). Total ten bags were prepared in the study.…”
Section: Substrate Preparationmentioning
confidence: 99%
“…Fr.) Kumm revealed that spawn run required 23.50 ± 1.27 days Dhakal et al (2020). reported that spawn run of P. ostreatus (Jacq.…”
mentioning
confidence: 99%
“…Oyster mushroom fruit body weight produced in this study ranged from 14.55-15.81 g. One of the factors that can affect the weight of oyster mushrooms (Pleurotus ostreatus) is the level substrate humidity which can also be affected by the frequency of watering (Saputera et al, 2020) and temperature. The growth of fruit bodies requires high humidity, which ranges from 80-90%, and moderate temperatures, which is between 25-30oC during the incubation period, while the period of fruiting body formation requires a lower temperature of 18-25 o C. (Dhakal et al, 2020). According to Saputera et al (2020), Oyster mushroom fruit weight is influenced by water content in the fruit body of oyster mushroom (Pleurotus ostreatus).…”
Section: Oyster Mushroom Production (Pleurotus Ostreatus)mentioning
confidence: 99%